Antibacterial Activity Against Acne Involved Bacteria of Chitosan in a Soluble State and as Nanoparticles - Supreedee Sungkharak (Science Faculty of Chiang Mai University, 2019)
Chitosans with different molecular weights (MW) in the range of 10 kDa -500 kDa from two sources in a soluble state and as chitosan nanoparticles were investigated for their antibacterial activities against three bacteria involved in acne namely Propionibacterium acnes, Staphylococcus aureus, and Staphylococcus epidermidis. Chitosans in a soluble state showed antibacterial effects with the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values ranged from 15 to 125 mg/mL. The antibacterial activities were dependent on the MW, the sources of the chitosan and the type of bacteria. The antibacterial activity was enhanced as the MW increased. In addition, the sources of chitosan had a marked influence on the antibacterial activity against P. acnes and S. epidermidis. Chitosan nanoparticles exhibited higher antibacterial activity than the solution form. The MIC and MBC values ranged from 0.25 to 31 mg/mL depending on their particle size in that small chitosan nanoparticles (<200 nm) had higher antibacterial activity than larger chitosan nanoparticles (>200 nm). Chitosan in both a soluble form and nanoparticles has potential to use as an anti-acne agent due to their antibacterial properties.